Skeletal Dysplasias Caused by Sulfation Defects - Chiara Paganini (International Journal of Molecular Sciences, 2020)
Proteoglycans (PGs) are macromolecules present on the cell surface and in the extracellular matrix that confer specific mechanical, biochemical, and physical properties to tissues. Sulfate groups present on glycosaminoglycans, linear polysaccharide chains attached to PG core proteins, are fundamental for correct PG functions. Indeed, through the negative charge of sulfate groups, PGs interact with extracellular matrix molecules and bind growth factors regulating tissue structure and cell behavior. The maintenance of correct sulfate metabolism is important in tissue development and function, particularly in cartilage where PGs are fundamental and abundant components of the extracellular matrix. In chondrocytes, the main sulfate source is the extracellular space, then sulfate is taken up and activated in the cytosol to the universal sulfate donor to be used in sulfotransferase reactions. Alteration in each step of sulfate metabolism can affect macromolecular sulfation, leading to the onset of diseases that affect mainly cartilage and bone. This review presents a panoramic view of skeletal dysplasias caused by mutations in genes encoding for transporters or enzymes involved in macromolecular sulfation. Future research in this field will contribute to the understanding of the disease pathogenesis, allowing the development of targeted therapies aimed at alleviating, preventing, or modifying the disease progression.